2010
DOI: 10.1007/s11103-010-9682-8
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hsp100/ClpB-like proteins: poorly-analyzed cousins of yeast ClpB machine

Abstract: ClpB/Hsp100 proteins act as chaperones, mediating disaggregation of denatured proteins. Recent work shows that apart from cytoplasm, these proteins are localized to nuclei, chloroplasts, mitochondria and plasma membrane. While ClpB/Hsp100 genes are essentially stress-induced (mainly heat stress) in vegetative organs of the plant body, expression of ClpB/Hsp100 proteins is noted to be constitutive in plant reproductive structures like pollen grains, developing embryos, seeds etc. With global warming looming lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…In this study, matrices corresponding to HSF bindings sites were noted in the promoters of several DEGs in response to CS, HS and OS (Tables 3, 4) suggesting that HSFs are major players in the stress response. It has earlier been noted that HSPs are induced by a variety of stress conditions [21], [40], [59][63]. Wang et al [64] has proposed that a cross-talk exists between HSP/chaperone and other stress responsive mechanisms in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, matrices corresponding to HSF bindings sites were noted in the promoters of several DEGs in response to CS, HS and OS (Tables 3, 4) suggesting that HSFs are major players in the stress response. It has earlier been noted that HSPs are induced by a variety of stress conditions [21], [40], [59][63]. Wang et al [64] has proposed that a cross-talk exists between HSP/chaperone and other stress responsive mechanisms in plants.…”
Section: Discussionmentioning
confidence: 99%
“…ScHsp104 expression during HS and metal toxicity is independently mediated by the heat shock factor 1 (Hsf1) and Msn2/Msn4 transcriptional activators, respectively. Hsf1 binds to two heat shock elements (HSEs) and Msn2/Msn4 binds to three stress responsive elements (STREs) present in the ScHsp104 promoter (Singh & Grover, 2010). In maize, five HSEs were reported within the proximal 289 bases of the ZmClpB-C promoter region (Nieto-Sotelo et al, 1999).…”
Section: Genetic Regulation Of Clpb-c Gene Expressionmentioning
confidence: 99%
“…They are localized to different subcellular compartments, such as cytoplasm, nucleus, mitochondria and plasma membrane (Singh & Grover, 2010). Interestingly HSP100 proteins and also their homologues are absent in Archaea (Large et al, 2009), but they are found in Bacteria and Eukaryotes (Barends et al, 2010).…”
Section: Hsp100 Familymentioning
confidence: 99%